Testing a behaviourally informed product comparison tool for private health insurance - Olga Poluektova; Martina Barjaková; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
The market of private health insurance is characterised by high level of consumer inertia. Low consumer activity is probably linked to product complexity, abundance of choice options and low consumer understanding. These factors may overwhelm consumers and reduce willingness to engage with the process of choosing private health insurance. To address this issue, we designed a behaviourally informed health insurance plan comparison tool that splits the decision into sequential stages, aiming to make the process of choice easier and less frustrating. In a pre-registered online experimental study, we tested this tool against one that closely mimicked the market regulator's existing online comparison tool. Our results revealed higher satisfaction with and clear preference for the behaviourally informed comparison tool, across different sociodemographic groups. We also found a small but significant positive effect of the sequential tool on satisfaction with the chosen health insurance plan. Consumers using the sequential tool opted, on average, for lower premiums. Overall, our findings attest to the usefulness of decision aids based on the principles of sequential decision making, both for consumer satisfaction and choice outcomes.
Keywords: 330; private health insurance; choice overload; sequential decision-making; decision aids